Infiltration Wells Effectiveness Analysis: Study in Purwantoro Village, Malang City - Oxike Morillyn; Moh. Khusaini; Vietha Devia; Bunga Hidayati (Postgraduate, University of Mataram, 2024)
Infiltration wells are one of the effective infrastructure in draining rainwater so that they can reduce waterlogging, but existing infiltration wells need to be reviewed for their effectiveness as water shortages are still occurring especially in the Purwantoro Village.The study aims to determine the effectiveness of Infiltration wells and calculate the appropriate number of infiltration wells in Purwantoro Village. The method used in this research is a hydrological analysis, planned flood discharge analysis dan infiltration well effectiveness analysis. The results of the study showed that the effectiveness of existing infiltration wells in Purwantoro Village varies greatly, with the highest at 82.8% and the lowest at 11.3%. To increase the effectiveness of infiltration wells, as many as 109 infiltration wells are needed in Purwantoro Village to reduce waterlogging. The conclusion of this study is the lack of effectiveness of infiltration wells in Purwantoro Village because the number of infiltration wells is still limited, so it is necessary to add infiltration wells and maintenance of infiltration wells is needed to reduce deposits contained in infiltration wells.